Diversity and training - Hidalgo Urrea, Esperanza (2011)
This article discusses the psychologists’ ethical training importance against psychotherapeutic  demands diversity of the contemporary world. The main objective is to analyze the possible relationship between the psychologist’s training and the diversity of psychotherapies that currently exist. Representative authors’ published literature, results from different studies and working papers have been taken into account to write this article. It is concluded that in order to preservethe practice of psychology and its deviations motivated by external demands, it is necessary not only a growing strength of the epistemological foundations of psychology, but also an ethical training of psychologists, not a “doit être” but transcending to “être” as an essential requirement, regardless of their theoretical orientation, given the importance of professional act and the implications it has on others.